Long Bone Open Fractures among Orthopedic Trauma Patients Presenting in a Tertiary Care Center: A Descriptive Cross-Sectional Study - Shrestha, Babu Kaji; Regmi, Subhash; Joshi, Sachindra Raj (Nepal Orthopaedic Association Journal, 2024)
Background: Management of open fractures often presents a challenge to the treating surgeon due to the complexity of the injury and the risk of infection associated with it. Familiarity with the patterns of open fracture enhances preparedness and thus improves the outcome. Hence, this study aims to determine the prevalence of open fractures among patients presenting in the emergency department of a tertiary care center. Method: This was a descriptive cross-sectional study conducted at B&B Hospital, Lalitpur, Nepal, from January 2020 to Dec 2023, where data of patients with long bone open fractures were retrospectively retrieved from the hospital’s computerized database. Data included Demographic details, location of the fracture, Gustilo Anderson classification, the pattern of fracture, and associated injury. The analyses of different variables were done according to standard statistical analysis. Results: Of 2572 patients with long bone fractures, 305 had open fractures (11.9%). The mean age was 33.65 ± 16.30 (5-84)years. Males accounted for 84.6% of the cases. Road traffic accidents accounted for 88.2% of cases. Most of the openfractures occurred in the lower limb (84.9%); also, open fractures of the tibia and fibula accounted for 43% of the cases.According to Gustilo Anderson’s Classification, Type I accounted for 22.6% of cases, Type II was 31.5%, Type IIIA was25.2%, Type IIIB was 15.4%, and Type IIIC was 5.2%. Wedge and Comminuted patterns of fracture accounted for 70%of cases. Also, 140 (45.9%) cases had associated other injuries, and 15.1% of cases had associated long bone fractures. Conclusion: Open fractures had male predominance and were mostly caused by road traffic accidents. This study describesthe location, type, and patterns of open fracture, where the tibia and fibula were more usually involved; Gustilo AndersonType III was the most common type, and the frequently seen fracture pattern was wedge/ comminuted.